Elipse como lugar geométrico en un ambiente de geometría dinámico - León Ríos, José Carlos (2018)
In this document we present the results of a research that aimed to enhance in the students' the development of dynamic thinking about the variational nature of mathematical knowledge. We presented situations involving changes and regular patterns in the quantities studied when passing from one state to another, and whose study required students to develop cognitive processes that explain, speculate, argue, share and model the meaning of the objects under analysis. We will present the case of the geometric condition of the ellipse for students in pre-calculus courses in an environment of dynamic geometry using GeoGebra as a mediator instrument. To demonstrate the use of different representations we use as a reference, the Semiotics Representation Register which analyzes the role of signs as representative records of mathematical objects.